PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN CUNGKRUNGAN DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , HABIBULLOH KHOMEINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Situation map contains the spatial information that describes the state of a region on the surface of the earth which is manifested through symbols such as points, lines, areas, and attributes. Situation map is often used as a source of information for planning in a job. The purpose of the implementation of the Field Practice (PKL) is making large-scale map of the situation through terrestrial measurement and delineation using digital technology. PKL is a means of students to apply their knowledge of science so adept at doing situation map-making. Stages in the map-making situation began with the manufacture of basic mapping framework that includes measuring Horizontal Control Framework (KKH) and Vertical Control Framework (KKV), then proceed to the stage of measurement points covering detailed planimetric detail and high detail, calculating the measurement data, digital cartography using Surpac software and ArcGIS and test the map. Testing is done by testing the accuracy of the map distance and height difference test with a tolerance of 90% from TOR. Measurement data is realized in the form of a situation map scale of 1:500 Cungkrungan Hamlet, Beluk Village, Bayat Sub-District, Klaten District printed on A1 paper size. Based on the test map that includes distance accuracy and testing of different test high, the results obtained do not meet the TOR, so that the resulting situation maps have poor quality and not represent the actual state.